IMPLEMENTATION OF BLANDED LEARNING MODEL BASED ON EDMODO APPLICATION TO IMPROVE ENGLISH FOR SPECIFIC PURPOSE (ESP) LEARNER’S INTEREST - Merlin Djamal (Jurnal Bahasa Lingua Scientia, 2018)
The purpose of this study was to determine the implementation of information and communication technology in the form of the academic networking site-Blended learning Model Based Edmodo on learner engagement and responsible learning. This research evaluated whether Edmodo should be employed by more lecturer hoping to encourage a learner’s interest in learning English for Specific Purpose. The study was conducted at STIE Muhammadiyah Tanjung Redeb Berau. The population were 1500 degree learners, out of which 21 learners of Accounting Department was taken for the analysis as they fall under the Edmodo users. This research study used qualitative method and a research designed survey was administered to gather questions with answers associated with a 5-point Likert scale ranging from strongly agree to disagree strongly. The result of the study showed that Edmodo helped reduce the workload as a lecturer and made it easier to stay connected with our classroom and our learners. The results of this study may inspired lecturers to reappraisal the way they conducted their classes.